A combined force field for the silica/nickel system. Issue 3 (11th February 2020) - Damián-Vázquez, Sergio; Alvarado, Juan F. J.; Castrejón-González, Edgar O.
ABSTRACT: Silica and nickel are frequently used in the synthesis of carbon nanotubes by the chemical vapour deposition (CVD) process. The molecular simulation of this process requires the knowledge of force fields to model the interactions occurring between those species at the atomic scale. This work proposes a combined force field to model the silica/nickel system when these components are in contact as substrate and catalyst, respectively, in the CVD process. The proposed combined force field includes the Lennard–Jones ( n–m ) potential for modelling the silicon/nickel pair interactions and the Buckingham potential for the oxygen/nickel pair interactions. The combined force field is completed by the Tersoff potential to model silica (SiO2 ) and the Sutton–Chen potential for the cohesive forces present in the nickel clusters. Parameters for the Lennard–Jones ( n–m ) and Buckingham pair potentials were fitted, by the least squares technique, to interaction energies data for the silica/nickel system. The energies were obtained from Ab-initio (DFT) calculations using the VASP code. It was found that the combined force field reproduces adequately, by molecular dynamics simulation, the adherence (adsorption) of nickel clusters on the silica surface. Keeping stable this configuration is crucial in modelling the carbon nanotubes synthesis by the CVD process.